IMPLEMENTASI NILAI TRILOGI UKHUWAH KH. ACHMAD SHIDDIQ PADA MATA PELAJARAN PPKn DALAM MEMBENTUK KARAKTER PERSAUDARAAN SISWA DI SMP ISLAM MENARA AL-FATTAH - Fikri Cahyono, Erik; Andrie Djatmiko, Andreas (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study explores the implementation of KH. Achmad Shiddiq's Trilogy of Ukhuwah values in shaping the brotherhood character amidst the sociological complexity of students at SMP Islam Menara Al-Fattah. The sharp heterogeneity, encompassing residence status differences, family social stratification, and the existence of inclusive students, demands precise pedagogical intervention within the Pancasila and Civic Education (PPKn) subject. Utilizing a qualitative approach with a descriptive case study design, the researcher acted directly as the key instrument and practitioner (participant-as-observer). Data collection was conducted through active participant observation, in-depth interviews, and document review, subsequently analyzed using the interactive model of Miles, Huberman, and Saldana. The findings indicate that the integration of the Trilogy of Ukhuwah successfully constructed Thomas Lickona's three character dimensions. Ukhuwah Islamiyah fostered moral knowing through humanistic conflict resolution; Ukhuwah Wathaniyah shaped the moral feeling of equality via heterogeneous group discussions; and Ukhuwah Basyariyah triggered moral action through peer-tutoring practices for inclusive students. Primary obstacles, including early adolescent egocentrism and the permissive tradition of ghosob, were effectively mitigated through the educator's persuasive approach, affective mentoring in a micro-scale class, and the students' theological homogeneity.